FAKTOR â FAKTOR YANG MEMPENGARUHI KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN PADA LAPORAN KEUANGAN (Studi Kasus Pada Pemeriksa BPK Perwakilan Provinsi Jawa Tengah) - Bagus Kundianto, 13.05.52.0262; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
The purpose of this research is to analyse the influence of independency, audit experience, professional skepticism, competency, time pressure and workload towards auditorâs ability to detecting fraud on the auditor BPK Representative of Province in Central of Java. The population of this research are all auditor which have followed Education and Training of Functional Posision of Auditor (JFP) and 2 years minimal job experience as auditor. Sampling was conducted using a purposive sampling method and number of samples of 98 respondents. Primary data collection method used is multiple regression model. The result showed that audit experience, competency and time pressure have a position impact on auditorâs ability to detecting fraud. And independency, professional skepticism and workload doesnât have a position impact on auditorâs ability to detecting fraud.Keywords: Independency, Audit Experience, Professional Skepticism, Competency, Time Pressure, Worload, Auditorâs Ability, Detecting Fraud